2018
DOI: 10.1177/1103308818787647
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the Uniform: Youth Attitudes towards Military Service in Israel

Abstract: Military service is one of the key milestones in Jewish Israelis’ transition to adulthood. Given the dominant role of the military in Israeli society, an understanding of young adults’ attitude towards the importance of the military and the nature of their service is needed. Based on 44 group interviews with 132 Jewish Israeli high school students, the study follows the differential attitude of youths towards compulsory military service, along socioeconomic lines. It concludes that (a) despite changes in Israe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The literature indicates that Israeli soldiers perceive military service as a means to personal development but also as a stepping stone to professional experience (Girsh, 2018). The findings of the research revealed that the perception of military service and the expectation of Israeli combat soldiers to convert acquired military capital were similar to those of British combat soldiers and soldiers without professional certification, that is, with no conversion rate to labor market.…”
Section: Soldiers' Perceptions and Expectations Of Converting Military Capitalmentioning
confidence: 84%
“…The literature indicates that Israeli soldiers perceive military service as a means to personal development but also as a stepping stone to professional experience (Girsh, 2018). The findings of the research revealed that the perception of military service and the expectation of Israeli combat soldiers to convert acquired military capital were similar to those of British combat soldiers and soldiers without professional certification, that is, with no conversion rate to labor market.…”
Section: Soldiers' Perceptions and Expectations Of Converting Military Capitalmentioning
confidence: 84%
“…The idea of service for the society and state is instrumental in achieving this. This is also evident in Girsh’s (2019) analysis of Jewish Israeli youth’s attitudes toward their prospective military service, seeing it ‘as a necessary component of their normative citizenship’ (p. 304). While this is typical for the republican discourse of civic education, this study also exposes the liberal stance that is entangled in the notion of a ‘meaningful service’.…”
Section: Discussion and Conclusion – ‘We Are All Partners In This Sha...mentioning
confidence: 98%
“…In the Israeli case what is often neglected from both discourses is a critical point of view toward the militaristic ethos (Eastwood, 2017; Girsh, 2019; Lemish, 2003). However, negation of a critical stance in civic education, and specifically regarding social injustices such as racism and inequality, is not unique (Banks, 2017; Snir and Eylon, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The study was approved by the IDF Human Research Review Board and by the Committee of Human Subject Research of the Medical Corps Helsinki Committee (No. 1987(No. -2019.…”
Section: Discussionmentioning
confidence: 99%
“…The Israeli Defense Forces (IDF) are a unique setting for examining the matter of seeking mental health treatment. Given that service in the IDF is mandatory, it is a socialization milestone in Jewish Israelis' transition to adulthood (Girsh, 2019 ; Mayseless & Scharf, 2003 ). Thus, young Israeli soldiers may avoid seeking help for fear this could lower their medical profile and interfere with their military future (e.g., combat jobs, becoming officers, and proceeding to career service).…”
Section: Introductionmentioning
confidence: 99%